2021
DOI: 10.3390/plants10050845
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Stress Affects Photosynthesis, Malondialdehyde Formation, and Proline Content in Portulaca oleracea L.

Abstract: In this investigation, the effect of salt stress on Portulaca oleracea L. was monitored at salinity levels of 100 and 300 mM NaCl. At a concentration of 100 mM NaCl there was a decrease in stomatal conductance (gs) simultaneously with an increase in CO2 assimilation (A) at the beginning of salt exposure (day 3). However, the leaf water potential (ψw), the substomatal concentration of CO2 (Ci), the maximum quantum yield of photosystem II (Fv/Fm), and the proline and malondialdehyde (MDA) content remained unchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(73 citation statements)
references
References 72 publications
(79 reference statements)
15
57
0
1
Order By: Relevance
“…Interestingly, “746” and “747” showed the maximum content at 100 mM NaCl, while in landrace “751”, MDA content reached its peak at 300 mM NaCl. Such findings are in total agreement with the previously reported inconclusive differences in MDA level in purslane plants subjected to varying salt stress levels, where the MDA content showed a peak after exposure at 300 mM NaCl for 6 or 9 days [ 57 ]. In general, the increased MDA and O2- synthesis under salt stress has been associated with damage to cell membrane integrity and protein activity, although the damage recorded depends on the stress period [ 58 ].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, “746” and “747” showed the maximum content at 100 mM NaCl, while in landrace “751”, MDA content reached its peak at 300 mM NaCl. Such findings are in total agreement with the previously reported inconclusive differences in MDA level in purslane plants subjected to varying salt stress levels, where the MDA content showed a peak after exposure at 300 mM NaCl for 6 or 9 days [ 57 ]. In general, the increased MDA and O2- synthesis under salt stress has been associated with damage to cell membrane integrity and protein activity, although the damage recorded depends on the stress period [ 58 ].…”
Section: Discussionsupporting
confidence: 93%
“…These results also illustrate the higher antagonistic interaction of N with Na and Cl that might have improved the assimilatory function of the nitrogenous biochemical machinery, leading to an increase in the nitrogen yield efficiency, physiological nitrogen efficiency, photosynthetic nitrogen use efficiency, and nitrogen harvest index. This indicates that the increased concentration of N balanced the photosynthetic system under salinity stress through assimilation of carbon dioxide to increase stomatal conductivity in the C plant skeleton [25,68,69]. Similar results were also reported by Song et al [70], attributing improved NUE to optimal N supply in oat plant under salinity stress.…”
Section: Discussionsupporting
confidence: 85%
“…Abiotic factors, including salinity, reduce the photosynthetic rate. Elevated levels of NaCl also hamper stomatal function, uptake of CO 2 and ultimately photosynthesis ( Hnilickova et al, 2021 ). In the present study, a reduction in photosynthetic pigments was markedly observed under salinity stress in the tested okra varieties.…”
Section: Discussionmentioning
confidence: 99%